Aiming beyond the written, to the writer and writing: The writing consultation as a mentoring process for life-long writing - Banda, Collium (Stellenbosch Papers in Linguistics Plus, 2019)
This article critically reflects on how writing centres can address the notion that their primary role is to deal with students struggling with their writing. This critical reflection focuses on the following question: how can writing centres challenge the view that they exist primarily to assist students struggling with or lacking the academic writing skills required at university level? This question is answered from a theoretical framework of writing consultancy as a process of identity change. Presenting the writing consultation as a mentoring process for life-long writing, the article describes the author’s experiences of students who viewed the writing centre as a place for students who lack good writing skills. The article further examines some steps that may be taken to de-stigmatise writing centres, and promote them as places of identity change and empowerment. The article envisages that when the writing consultation is viewed as a mentoring process, writing centres may appeal to the greater university population, even students who are competent writers who would normally never see the need to consult writing centres.